Persistent Respiratory Distress in the Term Neonate: Genetic Surfactant Deficiency Diseases - Magnani, Jessie E.; Donn, Steven M. (Current Pediatric Reviews, 2020)
Respiratory distress is one of the most common clinical presentations in newborns requiring admission to a Neonatal Intensive Care Unit (NICU). Many of these infants develop respiratory distress secondary to surfactant deficiency, which causes an interstitial lung disease that can occur in both preterm and term infants. Pulmonary surfactant is a protein and lipid mixture made by type II alveolar cells, which reduces alveolar surface tension and prevents atelectasis. The etiology of surfactant deficiency in preterm infants is pulmonary immaturity and inadequate production. Term infants may develop respiratory insufficiency secondary to inadequate surfactant, either from exposure to factors that delay surfactant synthesis (such as maternal diabetes) or from dysfunctional surfactant arising from a genetic mutation. The genetics of surfactant deficiencies are very complex. Some mutations are lethal in the neonatal period, while others cause a wide range of illness severity from infancy to adulthood. Genes that have been implicated in surfactant deficiency include SFTPA1, SFTPA2, SFTPB, SFTPC, and SFTPD (which encode for surfactant proteins A, B, C, and D, respectively); ABCA3 (crucial for surfactant packaging and secretion); and NKX2 (a transcription factor that regulates the expression of the surfactant proteins in lung tissue). This article discusses the interplay between the genotypes and phenotypes of newborns with surfactant deficiency to assist clinicians in determining which patients warrant a genetic evaluation.
Keywords: pulmonary